Body mass index and waist-to-height ratio cut-offs as predictors of high blood pressure in adolescents (Medical Journal of Indonesia, 2015)
Background: Obesity is associated with increased risk for high blood pressure (BP). Although a routine BP measurement is indicated for all children visiting pediatric practice, recognition of children particularly at risk may save times. The aim of this study was to assess the cut-off point for body mass index (BMI) and waist-to-height ratio (WHtR) to predict high BP in adolescents. Methods: We conducted a cross-sectional study on 928 children aged 11 to 16 years in Yogyakarta. BP were measured using standard technique described by The Fourth Report on The Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents. BMI was adjusted for age and sex using the WHO 2007 growth reference. WHtR was ratio of waist circumference related to height in centimeters. Receiver operating characteristic (ROC) curves were used to estimate the best cut-offs. Results: The best cut-off point for BMI-for-age Z-score (BMIZ) to predict high BP was 0.51 with sensitivity and specificity of 82% (95% CI = 78-86) and 76% (95% CI = 67-78) for systolic BP and sensitivity and specificity of 82% (95% CI = 78-86) and 72% (95% CI = 68-76) for diastolic BP. The best cut-off point for WHtR was 0.45, with sensitivity of 76% (95% CI = 67-78) and specificity of 74% (95% CI = 71-79) for systolic BP and sensitivity of 76% (95% CI = 72-80) and specificity of 70% (95% CI = 61-75) for diastolic BP.Conclusion: BMIZ of 0.51 and WHtR of 0.45 are the best cut-off point to predict high BP in adolescents.